The Effect of Leadership and Organizational Culture on Employee Performance at the Ministry of Law Office in Makassar, South Sulawesi - Al Jibra, Muhammad Priya Brady; Akhmad, Akhmad; Rizal, Samsul (Dinasti Publisher, 2025)
This research is entitled “The Effect of Leadership and Organizational Culture on Employee Performance at the Makassar Kemenkum Office, South Sulawesi.” This research is motivated by the importance of human resource management in increasing organizational productivity, especially through effective leadership and a strong organizational culture. This study aims to analyze the effect of leadership and organizational culture on employee performance. The research method used was a quantitative approach with data collection techniques through questionnaires, which were distributed to 69 respondents who were employees of the Makassar Kemenkum Office. The data were analyzed using multiple linear regression with the help of the SPSS version 25 application. The results showed that leadership and organizational culture had a positive and significant effect on employee performance. This finding indicates that the better the application of leadership and the stronger the organizational culture, the employee performance will also increase. The conclusion of this study is that leadership and organizational culture are two important factors that need attention in efforts to improve employee performance in government agencies.